ShEŃGEL (HALIMODENDRON HALODENDRON PALL) ÓSIMLIGINIŃ BIO-EKOLOGIYALÍQ ÓZGEShELIKLERI - Baltabaev, Muratbay Tórebaevich; Końıratbaeva, Dilaram Baxadir qızı (SCIENCE and SOCIETY, 2026)
The article describes the biological and ecological characteristics of the Halimodendron halodendron plant as a promising species in the conditions of Karakalpakstan. Its resistance to saline soils, drought, and a strongly developed root system are due to these characteristics, and by planting it on the dried bottom of the Aral Sea, we will be able to improve the ecosystem of this area. The cinquefoil plant is a perennial shrub that reproduces vegetatively from seeds and rhizomes.